Impact of corticosteroids on the efficacy of first-line pembrolizumab plus chemotherapy in patients with advanced non-small-cell lung cancer - Amytis Roboubi; Eric Wasielewski; Soraya Bordier; Amélie Turlotte; Geoffrey Pavaut; Arnaud Scherpereel; Alexis Cortot; Clément Gauvain (Therapeutic Advances in Medical Oncology)
Background: Systemic corticosteroids (SCs) are associated with reduced survival in patients with advanced non-small-cell lung cancer (NSCLC) receiving immune checkpoint inhibitor (ICI) monotherapy. However, the current first-line standard of care usually involves combined chemotherapy (CT) and ICIs, and the effect of SCs on survival under combined CT and ICI has never been studied. Objectives: To investigate the association between SC therapy and survival under CT-ICI in advanced-stage NSCLC patients. Design: We performed a multicenter retrospective cohort study of all advanced-stage NSCLC patients receiving first-line CT-ICI. Methods: The primary endpoint was progression-free survival (PFS) according to SC exposure status (⩾10 mg/day), adjusted in a multivariate Cox model for the following confounders: age, performance status, hospital admission prior to treatment, number of metastatic sites, brain metastases, bone metastases, PD-L1 status, and histological subtype. Multivariate analyses also explored the association between dosage and SC exposure duration and PFS. Results: Of the 193 included patients, 43 (22.3%) were receiving SCs, mainly because of symptomatic brain metastases (in 25/43 cases, 58%). In multivariate analysis, SC therapy at a 10 mg/day threshold was not associated with PFS (hazard ratio (HR) = 1.25, 95% confidence interval (CI) 0.77–2.03, p  = 0.35). However, SC dose was negatively associated with PFS (HR = 1.08 per 10 mg/day increment, 95% CI 1.01–1.16, p  = 0.01) especially at doses ⩾60 mg/day (HR = 3.27 per 10 mg/day increment, 95% CI 2.01–5.35, p  < 0.001). Duration of SC therapy was not associated with PFS (HR = 0.97, 95% CI 0.81–1.15, p  = 0.71), but SC therapy ⩾4 weeks prior to CT-ICI was associated with shorter PFS (HR = 1.07, 95% CI: 1.01–1.14, p  = 0.028). Conclusion: In this group of patients receiving first-line CT-ICI for advanced NSCLC, SCs at ⩾60 mg/day were associated with shorter PFS, but lower doses were not. Prolonged SC therapy prior to CT-ICI was associated with shorter PFS. Larger studies are required to confirm these results.